Pilomatricoma/Dermoid cyst. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2003)
Pilomatricoma is a benign tumor deriving from hair matrix cells, whereas dermoid cyst derives from epidermal residua. The latter remain in the dermis during the fetal life along the lines of fusion of the embryo.